Unilateralni trening za moč - Martinc, David (Šport (Ljubljana), 2016)
In the recent years the unilateral training has become an important and effective approach to the strength training. The purpose of the article was to conduct a review of researches from this field and to provide some practical guidance for training. In the introduction, we presented the researches, which dealt with the morphological and neural adaptations unilateral exercise of power. Inside neural adjustments we especially highlighted the bilateral deficit phenomenon and crossover effect. We also analyzed the most important researches in the field of comparisons in muscle activation between different bilateral and unilateral exercises as well as describe the effects of unilateral strength training on some forms of power. Unilateral training could be a very effective way to gain strength and can be incorporated into both the top and recreational sport as well as for therapeutic purposes.
Keywords: bilateral deficit; bilateralni deficit; cross effect; križni efekt; moč; sport; strength; šport; trening; unilateral training; unilateralni trening